Modeling and Simulation of Coke Combustion Regeneration for Coked Cr2O3/Al2O3 Propane Dehydrogenation Catalyst - 张新平 隋志军 周兴贵 袁渭康 (Chinese journal of chemical engineering, 2010)
A heterogeneous model is developed for the regeneration of the Cr2O3/Al2O3 catalyst for the propane dehydrogenation process by considering the internal mass transfer and external mass/heat transfer during the coke combustion.Simulation shows that under practical operating conditions,multi-steady states exist for the catalyst pellets and the catalyst temperature is sensitive to gas temperature.However,at increased mass flow rate or lowered oxygen concentration,multi-steady states will not appear.Under the strong influences of film diffusion,the coke in the packed bed reactor will first be exhausted at the inlet,while if the film diffusion resistance is decreased,the position of first coke exhaustion moves toward the outlet of the reactor.